BALATON and COMINO: Phase III Randomized Clinical Trials of Faricimab for Retinal Vein Occlusion - Lars-Olof Hattenbach, MD, PhD; Francis Abreu, PhD; Pablo Arrisi, PhD; Karen Basu, PhD; Carl J. Danzig, MD; Robyn Guymer, MD, PhD; Zdenka Haskova, MD, PhD; Jeffrey S. Heier, MD; Aachal Kotecha, PhD; Ying Liu, PhD; Anat Loewenstein, MD; András Seres, MD; et al. (Ophthalmology Science, 2023)
Purpose: Dual inhibition of angiopoietin-2 and VEGF-A with faricimab (Vabysmo) offers excellent visual acuity gains with strong durability in patients with diabetic macular edema (ME) and neovascular age-related macular degeneration. The phase III BALATON/COMINO (NCT04740905/NCT04740931) trials will investigate the efficacy, safety, and durability of faricimab in patients with ME due to retinal vein occlusion (RVO). Design: Two identically designed global, randomized, double-masked, active comparator–controlled studies. Participants: Anti-VEGF treatment-naive patients with branch, central, or hemiretinal RVO. Methods: Patients were randomized to 6 monthly injections of faricimab 6.0 mg or aflibercept 2.0 mg. From weeks 24 to 72, all patients received faricimab 6.0 mg administered in up to 16-week intervals using an automated treatment algorithm to generate a treat-and-extend–based personalized treatment interval dosing regimen. Personalized treatment interval adjustments were based on changes in central subfield thickness (CST) and best-corrected visual acuity (BCVA). Main Outcome Measures: Primary end point was noninferiority of faricimab versus aflibercept in mean change from baseline in BCVA (week 24; noninferiority margin: 4 letters). Secondary end points (weeks 0–24) were mean change from baseline in BCVA, CST, and National Eye Institute Visual Function Questionnaire 25 composite score; proportion of patients gaining or avoiding loss of ≥ 15/≥ 10/≥ 5/> 0 letters. Secondary end points (weeks 24–72) were treatment durability (week 68); continuation of weeks 0 to 24 end points. Ocular/nonocular adverse events will be assessed. Results: In total, 1282 patients across 22 countries were enrolled (BALATON, 553 patients, 149 centers; COMINO, 729 patients, 193 centers). Conclusions: Using a novel automated interval algorithm, BALATON/COMINO will evaluate the efficacy and safety of faricimab for ME secondary to RVO and provide key insights into how to personalize treatment. Financial Disclosure(s): Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.